2020
DOI: 10.1155/2020/8822534
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Dynamics of the Quadratic-Damping Helmholtz Oscillator

Abstract: In this paper, the Helmholtz equation with quadratic damping themes is used for modeling the dynamics of a simple prey-predator system also called a simple Lotka–Volterra system. From the Helmholtz equation with quadratic damping themes obtained after modeling, the equilibrium points have been found, and their stability has been analyzed. Subsequently, the harmonic oscillations have been studied by the harmonic balance method, and the phenomena of resonance and hysteresis are observed. The primary and secondar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…We also noticed the increase or decrease of these instability domains when the control parameters K; U of the control force of the system increase or decrease. )e effect of the control process on chaotic dynamic and on coexistence of attractors was effective with ε � −11 [32]. )e high amplitude of harmonic oscillations, chaotic states, and coexistence of attractors was successfully controlled by the passive control investigated in this work.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…We also noticed the increase or decrease of these instability domains when the control parameters K; U of the control force of the system increase or decrease. )e effect of the control process on chaotic dynamic and on coexistence of attractors was effective with ε � −11 [32]. )e high amplitude of harmonic oscillations, chaotic states, and coexistence of attractors was successfully controlled by the passive control investigated in this work.…”
Section: Discussionmentioning
confidence: 70%
“…In the presence of the control force, we plotted for the same parameters as Figures5(a), 5(c), and 5(d) for ε � 1 and Figures5(e) and 5(f ) for ε � −1. It noticed through these figures that the chaos is accentuated for ε � 1 but totally reduced for ε � −1[32].…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…In recent years, the nonlinear dynamics of this class of oscillators has been intensively studied, and interesting results such as perioddoubling leading to chaotic motion, strange attractors, reverse period-doubling bifurcation, symmetry breaking, antimonotonicity, existence of horseshoe chaos, and so on have been obtained [17][18][19][20][21][22][23][24][25]. In most of these studies, the Melnikov perturbation method [18,24,26,27] has been widely used to detect chaotic dynamics and to analyze nearhomoclinic motion with deterministic or random perturbation. is method is today considered as a powerful analytical tool to provide an approximate criterion for the occurrence of hetero/homoclinic chaos in a wide class of dynamical systems.…”
Section: Introductionmentioning
confidence: 99%
“…We made this choice because it has already been demonstrated that a modified Van der Pol-Duffing oscillator can be used to model the nonlinear chemical oscillations like BZ reactions [21][22][23][24][25][26]. Since the control of regular and irregular motions is an interesting issue in several areas [27], the dynamical behavior of a forced generalized Rayleigh oscillator, which constitutes a new model for describing the nonlinear chemical oscillations, may be investigated. For this, we use the Melnikov method to analyze the chaotic behavior of this new chemical oscillator.…”
Section: Introductionmentioning
confidence: 99%